Analisis Sistem Pengambilan Keputusan Penentuan Konstruksi Jalan dengan Perkerasan Kaku atau Fleksibel (Studi Kasus Jalan di Propinsi Maluku Utara) - Rivolino Merbas; Endang Widjajanti; Syahril Taufik (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
ABSTRACT This research discussing about decision support system analysis in determining concrete and composit road construction compared to asphalt construction for the case of roads in North Maluku Province. This study uses the Analytic Hierarchy Process (AHP) method or model as a method to analyze the feasibility of concrete and composit construction compared to asphalt construction. There are at least 7 (seven) factors that are considered as AHP inputs, namely road conditions, technical pavement, ecomonical/cost, duration/method of construction, availability of equipment, environmental conditions, and availability of materials. This study method includes data collection and analysis methods. For data collection, this study uses a questionnaire method that contains questions related to technical and non-technical factors that are used to assess the feasibility of a road for selecting a type of road pavement with flexible or rigid pavement. The construction feasibility of concrete and composite pavements is better than that of flexible asphalt pavements on road constructions, with the following sub-criteria conditions; roads that have bends and inclines, lower road maintenance costs, excellent weather and environmental resistance, less dense traffic, easy work execution and can be done at any time, do not require a lot of AMP and equipment, and asphalt availability can't fast time. The alternative of road pavement type is effective as a weight value of 33.78% with using the composite pavement construction. Keywords: Roadworthiness, Composite pavement, AHP, Decision Support System, North Maluku